STATE FINANCIAL CONTROL SYSTEM MORE IMPROVEMENT ISSUES - Vasila SH. Nuritdinova (American Journals Publishing, 2023)
The article discusses the issues of effective organization and financial management of budgetary organizations in conditions of limited state financial resources, the introduction of progressive, new methods of expenditure planning aimed at rational allocation and use of budgetary funds, and also provides recommendations on further improvement of the system of state financial control.
Keywords: state financial resources, budgetary institution, state financial control, budget allocations, department of Financial Control, program “Civil budget”, extra-budgetary funds.